Optimasi Pengambilan Keputusan dengan Neural Network: Menuju Era Keputusan Pintar - Akram Kemal Dewantara (The Indonesian Journal of Computer Science, 2024)
The ability to make quick and accurate decisions in the midst of a digital age laden with complex data is critical to success in various industries. In this research, a neural network-based reasoning system is developed to enhance the smart decision-making process. We developed a neural network architecture by utilizing the power of deep learning. This enables the processing of historical and real-time data. We also conducted case studies in healthcare, finance, and HR management to test how effective it is. The results show that, compared to conventional approaches, this method has a significant improvement in processing time efficiency and an increase in decision accuracy of up to 15%. These results show that neural networks have the ability to change the decision-making landscape and offer intelligent solutions to real-world problems.